2018
DOI: 10.2147/ijn.s157958
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of gold and silver nanoparticles from <em>Cannabis sativa</em> (industrial hemp) and their capacity for biofilm inhibition

Abstract: BackgroundCannabis sativa (hemp) is a source of various biologically active compounds, for instance, cannabinoids, terpenes and phenolic compounds, which exhibit antibacterial, antifungal, anti-inflammatory and anticancer properties. With the purpose of expanding the auxiliary application of C. sativa in the field of bio-nanotechnology, we explored the plant for green and efficient synthesis of gold nanoparticles (AuNPs) and silver nanoparticles (AgNPs).Methods and resultsThe nanoparticles were synthesized by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
147
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(162 citation statements)
references
References 50 publications
13
147
1
1
Order By: Relevance
“…Hashimoto et al [26] showed that silver nanoparticles inhibited biofilm formation by Streptococcus mutans, while no inhibitory effect was observed with Au NPs. Similar results were obtained by Singh et al [63] where AgNPs showed strong inhibitory activity against Escherichia coli and Pseudomonas aeruginosa biofilm formation, but the effect of AuNPs was much weaker.…”
Section: Discussionsupporting
confidence: 89%
“…Hashimoto et al [26] showed that silver nanoparticles inhibited biofilm formation by Streptococcus mutans, while no inhibitory effect was observed with Au NPs. Similar results were obtained by Singh et al [63] where AgNPs showed strong inhibitory activity against Escherichia coli and Pseudomonas aeruginosa biofilm formation, but the effect of AuNPs was much weaker.…”
Section: Discussionsupporting
confidence: 89%
“…The introduction of bio-mediated synthesis of the metal nanoparticles has revolutionized the overall nanoparticle fabrication process. Besides making the whole synthesis process very simple and cost effective, the employed green synthesis approach also circumvents environmental and health-related issues (Singh et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Several nanoparticles, such as ZnO, gold and silver nanoparticles, have been reported to possess strong antibiolm properties against Streptococcus pneumonia, E. coli and Pseudomonas aeruginosa. 38,39 They have also been widely exploited as novel bacteria-resistant products for the long-term disinfection of root canals, preventing the formation of E. faecalis biolms. 40 Most importantly, biolm-associated R. solanacearum cells can produce a variety of extracellular polymeric substances (EPS) along with various proteins, which are known to be key pathogenic factors when a pathogen infects host roots in the rhizosphere.…”
Section: Inhibition Of Bacterial Biolm Formationmentioning
confidence: 99%